MiR-384 Regulates the Th17/Treg Ratio during Experimental Autoimmune Encephalomyelitis Pathogenesis - Qu, Xuebin; Han, Jingjing; Zhang, Ying; Wang, Yuanyuan; Zhou, Jun; Fan, Hongbin; Yao, Ruiqin (Frontiers in Cellular Neuroscience, 2017)
Specific miRNAs are involved in the pathogenesis of multiple sclerosis (MS), during which IL-17-producing CD4+ T helper (Th17) cells accumulate in the central nervous system. In this study, we identified levels of miR-384 as significantly increased in mice with experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Over-expression of miR-384 in vivo led to severe EAE, characterized by exacerbated demyelination, and increased inflammatory cell infiltration of the spinal cord; inhibition of miR-384 reversed these changes. Both the percentage of Th17, and ratio of Th17/Treg, cells were elevated in miR-384-transfected EAE mice, which was consistent with the observed upregulation of expression of IL-17 and the Th17 lineage-specific transcription factor, RORγt. Importantly, transfer of miR-384 overexpressing naïve T cells from wild-type to Rag1–/– mice, which are deficient in functional autologous T and B cells, led to aggravated EAE pathogenesis, while an miR-384 inhibited group was protected from EAE. Moreover, miR-384 promoted differentiation of naïve T cells into Th17 cells in vitro. Furthermore, target prediction and dual luciferase reporter assays demonstrated that SOCS3, a gene encoding a protein with an established role in Th17 differentiation, was a direct target of miR-384. Our results demonstrate an important role for miR-384 in regulation of the Th17/Treg ratio during the pathogenesis of EAE, indicating that this molecule may have potential as a biomarker and/or therapeutic target in MS.